Numerical method for discrete double barrier option pricing with time-dependent parameters. (October 2015) - Farnoosh, R.; Sobhani, Amirhossein; Rezazadeh, Hamidreza; Beheshti, Mohammad Hossein
Abstract In this paper, the main purpose is pricing of discrete double barrier option under Black–Scholes framework with time dependent parameters. By some conventional transforms, in each monitoring interval, the problem is reduced to well-known Black–Scholes partial differential equations with convenient constant coefficient such that the solution can be expressed recursively upon the heat equation solution. Finally a numerical method is proposed to compute the obtained recursive formula efficiently. Also, the Greeks of contract are calculated.